Respuesta :

Answer:

              y = - 6(x - 3)² + 4

Step-by-step explanation:

The vertex form of  the equation of the parabola with vertex (h, k)   is:

y = a(x - h)² + k  

So  the equation of the parabola with vertex (3, 4):

y = a(x - 3)² + 4

The parabola passes through point (2, -2) so if x=2 then y=-2

- 2 = a(2 - 3)² + 4

- 2 -4 = a(-1)² + 4 -4

- 6 = a

So, the equation written in vertex form of a parabola with a vertex of (5, 7) that passes through (2, -2):

                                       y = - 6(x - 3)² + 4